Buffy the vampire slayer [videorecording (Blu-Ray)] - Whedon, Joss, 1964-; Swanson, Kristy; Sutherland, Donald, 1935-; Reubens, Paul, 1952-; Hauer, Rutger, 1944-2019; Perry, Luke, 1966-2019; Swank, Hilary; Arquette, David; Hayman, James; Burwell, Carter (20th Century Fox Home Entertainment, 2011)
Blonde, bouncy Buffy is your typical high school cheerleader - her goal is to 'marry Christian Slater and die' and nothing gets in her way when it's time to shop. But all that changes when a strange man informs her she's been chosen by fate to kill vampires.